Theatre in Education: Children as human beings in their own right: Chris Cooper in conversation with Betty Giannouli - Giannouli, Betty (Education & Theatre, 2022)
Chris Coοper discusses with Betty Giannouli the historical evolution of Theatre in Education (TiE) as a particular form of theatre art with a distinct pedagogical approach and methodology. He highlights its social and political aspect from its very beginning at Belgrade Theatre in Coventry, UK and outlines the trajectory of ΤiE from its heyday to its gradual decline. He also talks about his personal journey as the artistic director of Big Brum Theatre in Education Company, his work as a playwright as well as his unwavering focus on the fundamental principles of TiE. He refers to his relationship with ancient Greek dramatists and his choice to not avoid challenges when writing plays for children and young people. Finally, he comments on his fifteen-year experience in Greece within the framework of his cooperation with Porta Theatre and, more recently, with the National Theatre’s Young People’s Stage. The interview was given to Betty Giannouli, a member of the Editing Committee, in Athens in May 2022.